The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.5194/acp-2019-1193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An AeroCom/AeroSat study: Intercomparison of Satellite AOD Datasets for Aerosol Model Evaluation

Abstract: Abstract. To better understand current uncertainties in the important observational constraint to climate models of AOD (Aerosol Optical Depth), we evaluate and intercompare fourteen satellite products, representing 9 different retrieval algorithm families using observations from 5 different sensors on 6 different platforms. The satellite products, super-observations consisting of 1° × 1° daily aggregated retrievals drawn from the years 2006, 2008 and 2010, are evaluated with AERONET (AErosol RObotic NETwork) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 18 publications
0
47
1
Order By: Relevance
“…Around 78% of the Deep Blue retrievals are within the expected error range of ±0.05±0.20*AOD (Sayer et al, 2013). MODIS AOD data have been extensively used by the modeling and remote sensing scientific communities and inter-compared with a wide range of satellite AOD products (see Schutgens et al (2020) and references therein).…”
Section: Methodsmentioning
confidence: 99%
“…Around 78% of the Deep Blue retrievals are within the expected error range of ±0.05±0.20*AOD (Sayer et al, 2013). MODIS AOD data have been extensively used by the modeling and remote sensing scientific communities and inter-compared with a wide range of satellite AOD products (see Schutgens et al (2020) and references therein).…”
Section: Methodsmentioning
confidence: 99%
“…The result obtained with MODIS Terra is consistent with that of Levy et al [43], who found significantly larger bias for this satellite sensor compared to MODIS Aqua. Therefore, the MODIS Aqua AOD was generalized to represent the MODIS dataset by Schutgens et al [44]. However, Georgoulas et al [45] found that MODIS Terra AOD exhibited the best agreement with AERONET over the eastern Mediterranean.…”
Section: Validation Against Aeronetmentioning
confidence: 99%
“…We need to allow some flexibility in the time separation between data (here 3 hours) to ensure sufficient numbers of collocated data pairs for further analysis. Schutgens et al (2020) showed that shorter time separations greatly limited the number of pairs but did not substantially alter the correlation of satellite AOD with AERONET. On the other hand, longer time separations appear to negatively affect the correlation of satellite AAOD with AERONET, see Fig.…”
Section: Collocation and Analysis Methodologymentioning
confidence: 99%
“…Since an individual AERONET site cannot be expected to be representative for a 1 o × 1 o grid-box, satellite evaluation may be negatively affected. To select only sites with high representativity we use a list published in Kinne et al (2013) as described in Schutgens et al (2020), where we also describe some tests for its suitability (based on 14 satellite AOD products). The Kinne list was developed with the AERONET Direct Sun product (i.e.…”
Section: Aeronetmentioning
confidence: 99%